2007
DOI: 10.3349/ymj.2007.48.4.634
|View full text |Cite
|
Sign up to set email alerts
|

Association between Internal Carotid Artery Morphometry and Posterior Communicating Artery Aneurysm

Abstract: PurposeThe goal of this study was to directly measure the association between the internal carotid artery (ICA) morphometry and the presence of ICA-posterior communicating artery (PCOM) aneurysm.Materials and MethodsThe authors intraoperatively measured the length of the supraclinoid ICA because it is impossible to radiologically determine the exact location of the anterior clinoid process. We used an image analyzer with a CT angiogram to measure the angle between the skull midline and the terminal segment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
28
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 14 publications
1
28
0
Order By: Relevance
“…Mean internal diameter of cerebral arteries and vascular geometry are important in diagnosis and management of cerebral aneurysms, strokes and ischemia (17).…”
Section: Discussionmentioning
confidence: 99%
“…Mean internal diameter of cerebral arteries and vascular geometry are important in diagnosis and management of cerebral aneurysms, strokes and ischemia (17).…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17][18][19][20] Kasuya et al 13 used 3-D CT angiography to study anterior communicating artery complexes and found that aneurysms were associated with increased angles between the directions of flow in the A1 and A2 segments. Similarly, Ingebrigtsen et al 14 found aneurysms to be associated with larger branch angles.…”
Section: Discussionmentioning
confidence: 99%
“…Previous case series have demonstrated that morphological factors of surrounding vasculature are correlated with aneurysms formation. [10][11][12][13][14][15][16][17][18][19][20] However, the contribution of vessel morphology at the basilar apex to the risk of aneurysm formation is unique and has not been described before. To control for genetic and environmental contributions, we examined the basilar apex in patients with at least 1 aneurysm and compared those with or without a BTA.…”
mentioning
confidence: 99%
“…Although the MCA has been the subject of extensive anatomical studies for the last 200 years, it still remains incompletely described. Only a limited number of reports have addressed the features of its morphometry such as diameter and length (Tanriover et al, 2003; Kim and Kang, 2007). There are only few studies that have included the internal diameter of the MCA based on computed tomography (CT) or magnetic resonance (MR) angiography.…”
Section: Introductionmentioning
confidence: 99%